METODA ULTRASONIK UNTUK MENENTUKAN ARAH KRISTAL TUNGGAL BERSTRUKTUR KUBIK - Trisnobudi, Amoranto; Sugiharto, Benny (Mesin, 2000)
Single crystal direction can be determined by x-ray diffraction. The determination of this crystal direction can also be carried out by using ultrasonic method. In this method the ultrasonic wave velocity propagating through the crystal is measured. From this velocity measurement then the crystal direction can be determined. This paper deals with the results of a research about the direction determination of cubic single crystal using ultrasonic wave. There are two methods used, namely graphical method and computer method. These two methods used the same data, i.e. velocity data for all possible direction that has been calculated based on the wave and elasticity theory. In the ï¬rst method, the data are stored as several graphics whereas in the second method they are stored as database in a computer program. These two methods have shown the same results in aluminum for crystal directions [311], [331], [661], [631] and [611] where the computer method can be carried out quicker than the graphical method.